Targeted interventions in Rajasthan, India: How informed are the beneficiaries about transmission of human immunodeficiency virus/acquired immunodeficiency syndrome? - Singh L; Purohit N; Mishra N (Wolters Kluwer Medknow Publications, 2007)
Research Questions: What is the present level of knowledge among the high-risk groups regarding human immunodeficiency virus (HIV) transmission and what is the source of such knowledge? What role do the stakeholders play in enhancing their level of knowledge? Objectives: To assess the efficacy of interventions focused on high-risk groups, and to find out indications on the needs to work with the general population. Study Design : Community-based cross-sectional survey about transmission of HIV/acquired immunodeficiency syndrome (AIDS); Study Period: December 2002. Participants: 1792 respondents, which included 1001 truckers, 389 migrants, 206 street children, and 196 commercial sex workers (CSWs). Setting: In intervention sites under SACS in Rajasthan Analysis: Frequency distribution and Chi-square tests. Results: Knowledge about all the four methods of transmission of HIV/AIDS was found to be relatively poor among the targeted intervention subjects. Of those who knew about HIV/AIDS about 67 per cent of the spouses of out migrants (55%) over one-third of the in migrants (35%), 45 per cent of the female commercial sex workers and 0.8 per cent truckers knew about all the correct modes of transmission of HIV/AIDS. TV/Radio emerged as the main source of knowledge about the correct modes of transmission for most of the respondents. The state health services and NGO workers, though primarily responsible for imparting knowledge to the subjects were found to be playing marginal role in the same.